Associação dos níveis séricos de ácido úrico com a força muscular de idosos e com o Índice de Massa Muscular apendicular de indivíduos jovens, meia-idade e idosos participantes do National Health and Nutrition Examination Survey (NHANES) 1999 – 2002 - Nahas, Paula Cândido (2021)
Background: Aging promotes muscle strength and muscle mass loss, and oxidative stress can be one of the possible causes. On the other hand, uric acid (UA) is an important plasma antioxidant that appears to be associated with strength and muscle mass, but this evidence is still limited. Aim: To associate serum UA with muscle strength in older adults and, later, with the Appendicular Muscle Mass Index (AMMI) in young, middle-aged and older adults. Methods: Cross-sectional studies (study 1: n = 2361 individuals - 50 to 85 years; study 2: n = 7149 individuals - 20 to 85 years), from the National Health and Nutrition Examination Survey (NHANES) 1999–2000 and 2001–2002. UA was obtained by the colorimetric method; muscle strength was measured by the isokinetic knee extension test; and body composition was measured by Dual Energy X-ray absorptiometry, and AMMI was calculated using appendicular lean mass divided by the square of height. Linear regression analysis was performed to observe a possible association between UA quintiles with muscle strength and UA quartiles with AMMI, adjusted for potential confounders. Results: UA was positively associated with muscle strength in the total sample (p=0.007), men (p=0.044) and women (p=0.016). In addition, UA was also positively associated with AMMI in older men (p=0.009), but not for young and middle-aged individuals. Conclusion: Serum UA is positively associated with muscle strength in older men and women, and also positively associated with AMMI in older men.